The influence of genetic variability in IL1B and MIR146A on the risk of pleural plaques and malignant mesothelioma - Piber, Petra (Radiology and oncology (Ljubljana), 2020)
Asbestos exposure is associated with the development of pleural plaques as well as malignant mesothelioma (MM). Asbestos fibres activate macrophages, leading to the release of inflammatory mediators including interleukin 1 beta (IL-1%). The expression of IL-1% may be influenced by genetic variability of IL1B gene or regulatory microRNAs (miRNAs). This study investigated the effect of polymorphisms in IL1B and MIR146A genes on the risk of developing pleural plaques and MM. Subjects and methods. In total, 394 patients with pleural plaques, 277 patients with MM, and 175 healthy control subjects were genotyped for IL1B and MIR146A polymorphisms. Logistic regression was used in statistical analysis. Results. We found no association between MIR146A and IL1B genotypes, and the risk of pleural plaques. MIR146A rs2910164 was significantly associated with a decreased risk of MM (OR = 0.31, 95% CI = 0.13%0.73, p = 0.008). Carriers of two polymorphic alleles had a lower risk of developing MM, even after adjustment for gender and age (OR = 0.34, 95% CI = 0.14%0.85, p = 0.020). Among patients with known asbestos exposure, carriers of at least one polymorphic IL1B rs1143623 allele also had a lower risk of MM in multivariable analysis (OR = 0.50, 95% CI = 0.28%0.92, p = 0.025). The interaction between IL1B rs1143623 and IL1B rs1071676 was significantly associated with an increased risk of MM (p = 0.050). Conclusions. Our findings suggest that genetic variability of inflammatory mediator IL-1% could contribute to the risk of developing MM, but not pleural plaques.
Keywords: azbest; genetska variabilnost; maligni mezoteliom; plevralni izlivi